Safety not guaranteed [videorecording (Blu-Ray)] - Plaza, Aubrey, 1984-; Johnson, Jake, 1978-; Soni, Karan; Duplass, Mark; Trevorrow, Colin, 1976-; Connolly, Derek; Turtletaub, Marc (Sony Pictures Home Entertainment, 2012)
Three co-workers at a magazine seek to interview someone who placed an ad for time travel companionship.